Meeting the nutrition and water targets of the Sustainable Development Goals: achieving progress through linked interventions - Ringler, Claudia; Choufani, J.; Chase, C.; McCartney, Matthew P.; Mateo-Sagasta, Javier; Mekonnen, Dawit Kelemework; Dickens, C. (International Water Management Institute, 2018)
Water and nutrition are linked in multiple ways, but few of these interlinkages are well understood. What is, for example, the exact relationship between water pollution and health or between water resource management and nutrition? Even less is known about the interactions across these various linkages. The importance of better understanding these connections has been highlighted as we pursue the United Nations Sustainable Development Goals (SDGs), which challenge mankind to meet both water security as well as food and nutrition security goals, while also improving water-based ecosystems. It has become increasingly clear that progress toward these goals can only be achieved if measures in the food and nutrition space (SDG 2) do not constrain progress on water (SDG 6) and if measures undertaken to support targets under one of these SGDs also support the outcomes of the other. This paper provides an overview of water–nutrition linkages as reflected in the SDGs, and it identifies key gaps in these linkages and suggests a way forward to support the achievement of both water and nutrition goals and targets.